Creativity and innovation in the design of public service announcements: classification and design models - Skliarenko, Nataliia; Gryshchenko, Ivan; Kolosnichenko, Olena; Ostapenko, Natalia; Kolosnichenko, Marina (Creativity Studies, 2023)
In the study, we analyzed the relationship between creativity and innovation in the design of public service announcements. Their synthesis became the basis for the creation of dynamic visual communications that changed the perception of social message. Using widely known examples of public service announcements, we rethought the content and project features of such phenomenon as public service announcement from a design point of view. We consider innovative public service announcement as a set of dynamic processes which are based on different types of interactions. Therefore, we put a focus on the integration of visual communications with the environment and, moreover, with a human being as an integral part of the information message. The study resulted in the classification of innovations in modern social advertising, which is based on creative experiments related to composition, human sensory sensations, communication and environmental technology. It has been proven that the creation of creative artistic images is based on universal design models, formed as a result of the synthesis of design thinking and innovation and, therefore, they are suitable for solving a wide range of social problems. The study substantiates the system of strategic goals for the development of innovative public service announcements which are aimed at sustainable development of society.